1998
DOI: 10.1002/cbm.232
|View full text |Cite
|
Sign up to set email alerts
|

Dramatherapy for mentally disordered offenders: changes in levels of anger

Abstract: The aim of this study was to examine changes in levels of anger associated with a therapeutic theatre project. The population consisted of mentally disordered patients in a maximum security hospital, all of whom had a history of major violence. The subjects were being treated on a ward that specializes in psychotherapeutic interventions. Twelve young adult male patients, defined by structured interview for personality disorder and clinical diagnosis for mental illness, participated in a week‐long dramatherapy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…Participants reported to have better capacity to control their impulses at the end of program as well. Previous research has shown that cognitive behavioral therapy (CBT) was effective in reducing anger and aggression in various populations, such as incarcerated offenders (Blacker et al, 2008), forensic outpatients (Hornsveld et al, 2008), and individuals with mental illnesses or mild mental disabilities (Reiss, Quayle, Brett, & Meux, 1998;Taylor, Novaco, Gillmer, Robertson, & Thorne, 2005). Our research extends these findings by demonstrating that CBT can be effective in reducing anger and aggression for youth offenders as well.…”
Section: Treatment Changesupporting
confidence: 69%
“…Participants reported to have better capacity to control their impulses at the end of program as well. Previous research has shown that cognitive behavioral therapy (CBT) was effective in reducing anger and aggression in various populations, such as incarcerated offenders (Blacker et al, 2008), forensic outpatients (Hornsveld et al, 2008), and individuals with mental illnesses or mild mental disabilities (Reiss, Quayle, Brett, & Meux, 1998;Taylor, Novaco, Gillmer, Robertson, & Thorne, 2005). Our research extends these findings by demonstrating that CBT can be effective in reducing anger and aggression for youth offenders as well.…”
Section: Treatment Changesupporting
confidence: 69%
“…These studies have generally concluded that participation in arts‐in‐prisons programmes may have lasting positive effects for prisoners, ranging from increased self‐esteem and confidence, to reduced levels of anger and risk of self‐harm, to enhanced learning motivation, to improved levels of tolerance of others and a greater capacity to work in teams (see, further, Kennedy ; Reiss et al . ; Dawes ; Goddard ; Cox and Gelsthorpe ; Anderson and Overy ; Boswell, Poland and Moseley ; compare Miles and Clarke ; Digard and Liebling ). Whether or not these long‐term positive effects can be attributed to the programmes evaluated is debatable, however, given that the evaluations in question either did not employ a control group, or, in any case, did not avoid other methodological pitfalls such as small sample size, selection bias and/or sample attrition.…”
Section: Limitations Of Studiesmentioning
confidence: 97%
“…These include drama therapy, psychodrama, role play, and applied theatre practices. Within the area of offender rehabilitation, drama-based techniques have been found to be useful in developing interventions specifically devised to motivate offenders towards change (Antonowicz & Ross, 1994;Matarosso, 1997;Reiss, Quayle, Brett, & Meux, 1998). Geese theatre (UK) has integrated the work of Portuguese drama therapist Fernando Santos Vieira with Prochaska and DiClemente's (1986) stages of change model, to develop a group-based intervention for violent offenders.…”
Section: Improving Treatment Success In Offender Rehabilitation Progrmentioning
confidence: 99%